Application Of Cell-Based Screening For The Discovery Of Potential Anti Type 2 Diabetis Candidate From Malaysian Natural Product Using Ppar(Y) Ligand As Model - Chuah, Ban Chung (2017)
Peroxisome proliferator –activated receptor (PPAR)-γ activators are commonly used in type 2 diabetes therapy or even drug research as they improved the sensitivity of insulin receptors in cell. Since ancient, medicinal plants have been used to treat diabetes mellitus and recent research proved the efficacy of these preparations and some of which are remarkably effective . In this study, anti-type 2 diabetes properties of the methanol extract of a total of 300 Malaysian natural products were subjected to PPARγ transactivation activity assay using liver hepatocellular carcinoma (HepG2) cell as model and the activity was assessed through the intensity of the luminescence produced by peroxisome proliferator response element (PPRE) .